Estudio de prevalencia de escherichia coli enterohemorrágica en canales de vacuno y cerdo faenadas en la Región Metropolitana, Chile - Burgos, Marisol; Martínez, M. Cristina; Barría, Bernardita; Pérez, Marco; Ulloa, Marcelo; Vaquero, Alejandra; Ayala, Germán; Ojeda, Julio; Fuentes, David; Schenone, Hugo (Avances en Ciencias Veterinarias, 2003)
The purpose was to determine Enterohemorragic E.coli in carcasses inside Metropolitan Region of Chile. Sampling was done between April 2000-Dic 2001 in all slaughterhouses, the number of samples was determinated by Vetstat Statistic Program, 3% error and 5% significante, 250 g of meat was taken just after been slaughtered. Suspicious colonies were confirmed using biochemical tests for E. coli and confirmed ones were run by PCR. Citotoxin identification were done using specific primers for 348 bp and 581 bp regions for stxl and stxll genes. 406 samples were analyzed, 226 (56%) cattle and 180 (44%) pork. StxII gen presente were detected in two beef samples out ok 226(0.89%). ECEH prevalence in beef meat is occasional on the other hand the microorganism was not detected in pork, this could be due to the slaughtering good practices and properly handling of carcasses that has been implemented on slaughterhouses, as well aspermanent sanitary surveillance on this stablishments by SESMA. (Environmental Health Service of Metropolitan Region).